2000
DOI: 10.4049/jimmunol.165.6.3423
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Induction of the Chemokine Receptor CXCR4 by TGF-β1 on Synovial T Cells Contributes to Their Accumulation Within the Rheumatoid Synovium

Abstract: Chemokines and their receptors determine the distribution of leukocytes within tissues in health and disease. We have studied the role of the constitutive chemokine receptor CXCR4 and its ligand, stromal-derived factor-1 (SDF-1) in the perivascular accumulation of T cells in rheumatoid arthritis. We show that synovial T cells, which are primed CD45RO+CD45RBdull cells and consequently not expected to express constitutive chemokine receptors, have high levels of the chemokine receptor CXCR4. Sustained expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
262
1
3

Year Published

2001
2001
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 315 publications
(283 citation statements)
references
References 39 publications
17
262
1
3
Order By: Relevance
“…For example, TGF-β1 has been reported to induce the expression of CXCR4 on dendritic cells [17,18] . Similar results were also observed in eosinophils, CD4 + T cells , macrophages derived from monocytes [19][20][21] , and so on. Moreover, Javelaud et al found that TGF-β1 upregulated CXCR4 mRNA expression in melanoma cells [22] .…”
Section: Introductionsupporting
confidence: 70%
“…For example, TGF-β1 has been reported to induce the expression of CXCR4 on dendritic cells [17,18] . Similar results were also observed in eosinophils, CD4 + T cells , macrophages derived from monocytes [19][20][21] , and so on. Moreover, Javelaud et al found that TGF-β1 upregulated CXCR4 mRNA expression in melanoma cells [22] .…”
Section: Introductionsupporting
confidence: 70%
“…CXCR4 is rapidly up-regulated after both PHA stimulation and IL-2 priming. In the RA synovium, T cells are induced to express CXCR4, and transforming growth factor ␤ is demonstrated to be responsible for the expression (Buckley et al, 2000). These CXCR4-positive synovial T cells show better adherence to fibronectin in response to SDF-1 than PBL.…”
Section: Terada Et Almentioning
confidence: 99%
“…Only recently it was recognized that stromal cell-derived factor-1 (SDF-1), the only known ligand of CXCR4, also plays a role in inflammatory diseases like rheumatoid arthritis [4]. More than 90% of the infiltrating T cells in the inflamed synovial membrane and synovial fluid express CXCR4 [5].…”
Section: Introductionmentioning
confidence: 99%